Métodos alternativos para a determinação de sódio, potássio, cálcio e magnésio em biodiesel - Barros, Ariane Isis (2012)
This work aimed the development of alternative simple and low cost methods of sample preparation for the determination of Na, K, Ca and Mg in biodiesel by different instrumental techniques. Three different procedures for sample preparation were available: (i) dissolution in ethanol for the determination of Na, K, Ca and Mg by atomic absorption spectrometry flame (FAAS); (ii) emulsion formation , using monoethanolamine (MEA) as tensoactive, for the determination of Na and K by FAAS and atomic emission spectrometry flame(FAES); (iii) liquid-liquid extraction, with aqueous solution of HNO3 (1%, v:v) as the extraction phase for determination of Na, K, Ca and Mg by FAAS and by ion chromatography (IC) with conductivity detector and Na and K by FAES. All the proposed methods allowed the use of aqueous inorganic standards. The analytical curves were linear with correlation coefficients (r) greater than 0.99. The limits of detection (LOD) and quantification (LOQ) were less than 3.40 mg kg-1 and are suitable for the determination of these metals considering the limits established by the Brazilian legislation (Na + K and Ca + Mg = 5 mg kg-1). The percentage recovery obtained at the sample preparation procedures (i), (ii) and (iii) varied from 72 – 119%, with coefficients of variation (CV%) smaller than 16%. The quantification by IC was not possible due to the low conductivity of the extraction solutions, probably caused by solubilization of components of biodiesel in water. Among the procedures proposed liquid-liquid extraction was the best alternative for the determination of Na, K, Ca and Mg in biodiesel samples by FAAS, and may be useful, especially for small producers in quality control of that fuel.